Plasma phospholipid fatty acid concentrations and risk of gastric adenocarcinomas in the European Prospective Investigation into Cancer and Nutrition (EPIC-EURGAST). - Chajès, V; Jenab, M; Romieu, I; Ferrari, P; Dahm, C; Overvad, K; Egeberg, R; Tjønneland, A; Clavel-Chapelon, F; Boutron-Ruault, M; Engel, P; Teucher, B; et al. (2011)
BACKGROUND: Epidemiologic data suggest that diet is a risk factor in the etiology of gastric cancer. However, the role of dietary fatty acids, a modifiable risk factor, remains relatively unexplored. OBJECTIVE: The objective of this study was to determine the association of plasma phospholipid fatty acid concentrations, as biomarkers of exogenous and endogenously derived fatty acids, with the risk of gastric adenocarcinoma in a case-control study nested within the European Prospective Investigation into Cancer and Nutrition-Europe Gastric Cancer (EPIC-EURGAST). DESIGN: Fatty acids were measured by gas chromatography in prediagnostic plasma phospholipids from 238 cases matched to 626 controls by age, sex, study center, and date of blood donation. Conditional logistic regression models adjusted for Helicobacter pylori infection status, BMI, smoking, physical activity, education, and energy intake were used to estimate relative cancer risks. RESULTS: Positive risk associations for gastric cancer were observed in the highest compared with the lowest quartiles of plasma oleic acid (OR: 1.72; 95% CI: 1.01, 2.94), di-homo-γ-linolenic acid (OR: 1.92; 95% CI: 1.10, 3.35), α-linolenic acid (OR: 3.20; 95% CI: 1.70, 6.06), and the ratio of MUFAs to saturated fatty acids, as an indicator of stearoyl-CoA desaturase-1 enzyme activity (OR: 1.40; 95% CI: 0.81, 2.43). An inverse risk association was observed with the ratio of linoleic to α-linolenic acid (OR: 0.37; 95% CI: 0.20, 0.66). CONCLUSION: These data suggest that a specific prediagnostic plasma phospholipid fatty acid profile, characterized mainly by high concentrations of oleic acid, α-linolenic acid, and di-homo-γ-linolenic acid, which presumably reflect both a complex dietary pattern and altered fatty acid metabolism, may be related to increased gastric cancer risk.